DESIGN OF MONITORING BANKING COLLATERAL DATA USING RFID IN REAL TIME - iklil, mokhamad (STEKOM PRESS, 2024)
The aim of the research is to build a monitoring system prototype that can provide notifications in the system for collateral items that are lost or out of range within the monitoring distance of the RFID reader. so that each officer can know when the item is lost or out of reach based on the time recorded in the monitoring system. This is different from CCTV AI which can only record overall conditions and movements, but does not provide notification of loss or removal of collateral from the range of the RFID reader. Keywords: Collateral Goods, Reader RFID, Tag RFID, Cctv AI, Notification